Early detection of soluble CD27, BTLA, and TIM-3 predicts the development of nosocomial infection in pediatric burn patients - Penatzer, Julia A.; Alexander, Robin; Simon, Shan; Wolfe, Amber; Breuer, Julie; Hensley, Josey; Fabia, Renata; Hall, Mark; Thakkar, Rajan K. (Frontiers in Immunology, 2022)
Thermal injury induces concurrent inflammatory and immune dysfunction, which is associated with adverse clinical outcomes. However, these effects in the pediatric population are less studied and there is no standard method to identify those at risk for developing infections. Our goal was to better understand immune dysfunction and identify soluble protein markers following pediatric thermal injury. Further we wanted to determine which early inflammatory, soluble, or immune function markers are most predictive of the development of nosocomial infections (NI) after burn injury. We performed a prospective observational study at a single American Burn Association-verified Pediatric Burn Center. A total of 94 pediatric burn subjects were enrolled and twenty-three of those subjects developed a NI with a median time to diagnosis of 8 days. Whole blood samples, collected within the first 72 hours after injury, were used to compare various markers of inflammation, immune function, and soluble proteins between those who recovered without developing an infection and those who developed a NI after burn injury. Within the first three days of burn injury, innate and adaptive immune function markers (ex vivo lipopolysaccharide-induced tumor necrosis factor alpha production capacity, and ex vivo phytohemagglutinin-induced interleukin-10 production capacity, respectively) were decreased for those subjects who developed a subsequent NI. Further analysis of soluble protein targets associated with these pathways displayed significant increases in soluble CD27, BTLA, and TIM-3 for those who developed a NI. Our findings indicate that suppression of both the innate and adaptive immune function occurs concurrently within the first 72 hours following pediatric thermal injury. At the same time, subjects who developed NI have increased soluble protein biomarkers. Soluble CD27, BTLA, and TIM-3 were highly predictive of the development of subsequent infectious complications. This study identifies early soluble protein makers that are predictive of infection in pediatric burn subjects. These findings should inform future immunomodulatory therapeutic studies.